High-carbon ultrapure base material and preparation method thereof

High-carbon ultrapure base materials are prepared through converter smelting and LF refining, which solves the problem of high impurity content in high-temperature alloys, significantly improves the performance of high-temperature alloys, and meets the high-performance demand of high-end equipment for materials.

CN119956227APending Publication Date: 2025-05-09SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510205602.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The existing high-temperature alloys have a high content of impurities, which affects their high-temperature strength, oxidation resistance and corrosion resistance, and cannot meet the extreme requirements of high-end equipment for materials.

Method used

The high-carbon ultrapure base material was prepared by converter smelting → slag removal → LF refining carbon-increasing desulfurization → slag removal → RH vacuum degassing → continuous casting process. Through the deep dephosphorization and deep desulfurization processes, the content of P, S, and Al is significantly reduced.

Benefits of technology

It significantly improves the comprehensive performance of high-temperature alloys, significantly reduces the content of P and S, and meets the preparation needs of high-end high-temperature alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgy, and relates to a high-carbon ultra-pure base material and a preparation method thereof, and the preparation method of the ultra-pure base material sequentially comprises a converter smelting process, a first slagging-off process, an LF refining process, a second slagging-off process, an RH vacuum degassing process and a continuous casting process. The content of sulfur (S < = 0.0006%), the content of aluminum (Al < = 0.0050%) and the content of phosphorus (P < = 0.0020%) in the ultra-pure base material prepared through the method are extremely low, the content of P, S and Al in the ultra-pure base material is remarkably reduced compared with the content of P, S and Al in a conventional raw material pure iron, and the requirement for preparing high-end high-temperature alloy for special purposes is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a high-carbon ultrapure base material and a preparation method thereof. Background Art

[0002] High-temperature alloys are widely used in aerospace, energy and other fields. One of the most important factors affecting the performance of high-temperature alloys is the content of impurity elements. As the content of impurity elements in high-temperature alloys increases, their performance, such as high-temperature strength, oxidation resistance, and corrosion resistance, will decline sharply, and they cannot fully meet the extreme requirements of high-end equipment for materials, limiting their application under more demanding working conditions. The most effective way to improve the quality of high-temperature alloys and reduce the content of harmful impurities in high-temperature alloys is to choose high-quality raw materials.

[0003] The purity of the base material is crucial to the performance of high-temperature alloys. At present, pure iron is used as raw material for smelting high-temperature alloys. The impurity content in ordinary base materials is relatively high, and the control range of the main harmful elements is: S: 0.0030%-0.0060%, P: 0.0040%-0.0120%, Al: 0.010%-0.040%. At the same time, in order to ensure the carbon content when smelting high-temperature alloys, a carburizer needs to be added for carburization, and the carburizer will also bring in impurity elements. These impurities will be concentrated at the grain boundaries during the solidification of the alloy, reducing the mechanical properties and corrosion resistance of the alloy, and affecting the quality and reliability of the high-temperature alloy. It is extremely difficult to smelt high-purity base materials with extremely low contents of harmful impurity elements, especially P, S, and Al. Mastering its preparation technology is of great significance to improving the performance of high-end high-temperature alloys.

[0004] In view of the above problems, the present invention provides an ultra-pure base material with high carbon and extremely low sulfur, aluminum and phosphorus content and a preparation method thereof, aiming to improve the purity of the base material and the control accuracy of the carbon content, and apply the high-carbon ultra-pure base material to the preparation of high-temperature alloys, hoping to significantly improve the comprehensive properties of the high-temperature alloys so that they can better adapt to the high performance requirements of high-temperature materials in the fields of aerospace, energy and so on. Summary of the invention

[0005] The purpose of the present invention is to provide a high-carbon ultrapure base material and a preparation method thereof in view of the above problems.

[0006] The object of the present invention is achieved in this way: a high-carbon ultra-pure base material, the mass percentage of its components is: C: 0.60-0.70%, Si≤0.02%, Mn≤0.01%, P≤0.0020%, S≤0.0006%, Al≤0.0050%, O≤0.0025%, N≤0.0040%, Cr≤0.04%, Mo≤0.04%, Cu≤0.04%, W≤0.03%, V≤0.01%, Ti≤0.0015%; the balance is Fe and unavoidable impurities.

[0007] The preparation method of high carbon ultrapure base material is characterized by comprising the following steps: Step 1: Converter smelting: double slag method is used for smelting: in the primary slag making process, 35-45kg / t of lime, 20-25kg / t of lightly burned dolomite, 5-8kg / t of red mud balls, and 1.5-2.2kg / t of fluorite are added into the converter before adding iron, and after blowing pure oxygen for 6-8 minutes, silicon and manganese oxidation is completed, and before carbon and oxygen are intensively oxidized, a slag pouring operation is performed, and the amount of slag in the furnace after the slag pouring is completed is ≤50% of the total amount of slag before slag pouring; secondary slag making is performed after slag pouring, and 20-25kg / t of lime needs to be added into the secondary slag making, Lightly burned dolomite 10-15kg / t steel, high-quality scrap steel, i.e. pure iron return material, is added during the converter blowing process to control the temperature to 1640-1670℃, red mud balls, fluorite and lime are added to the ladle in a ratio of 3:1:3 before the converter tapping, and the added amount is controlled at 12-15kg / t according to the amount of molten steel. At the same time, argon is blown from the bottom of the ladle during the converter tapping process, and argon blowing and stirring are continued for 8-10 minutes after the tapping is completed. The argon blowing intensity is controlled at 600-800Nl / min. After the argon blowing and stirring are completed, the slag in the ladle is removed by slagging, and the residual slag after slagging is not more than 25% of the total slag; the weight of S at the end point of the double-blowing converter smelting The percentage is ≤0.0050%, and the weight percentage of P is ≤0.0015%; Step 2: LF refining: The LF treatment temperature is 1610-1630℃. During the LF refining process, 20-30kg / t of lime, 15-20kg / t of fluorite, Al particles and aluminum wire are added to make reducing slag for deoxidation and desulfurization to produce deep desulfurization refining slag. The deep desulfurization refining slag includes, by mass percentage, CaO: 60-65%, SiO2: 12-18%, Al2O3: 10-15%, MgO: 4-6%, CaF2: 6-7%. The weight percentage of S after LF refining is ≤0.0005 %, and the weight percentage of P is ≤0.0018%; Step 3: The slag removal process is controlled within 15-25min, and the slag retention is 10-30mm; Step 4: RH vacuum degassing: The cycle time is 20-25min under a vacuum degree of 6-10mbar, and the weight percentage of S after RH vacuum degassing is ≤0.0006%, and the weight percentage of P is ≤0.0020%; Step 5: Continuous casting: 200mm×200mm-240mm×240mm square billets are used for continuous casting. The process adopts protective casting, the superheat is controlled at 20-30℃, and the pulling speed is controlled at 0.85-1.05m / min.

[0008] The beneficial effects of the present invention are as follows: the high-temperature alloy prepared by the present invention through the process of converter smelting → slag removal → LF refining carbon increase and desulfurization → slag removal → RH vacuum degassing → continuous casting uses an ultra-pure iron base material with high carbon content (C: 0.60-0.70%), extremely low sulfur (S: ≤0.0006%), aluminum (Al: ≤0.0050%), and phosphorus (P: ≤0.0020%), which has a significantly increased carbon content compared with conventional raw material pure iron, and at the same time, the contents of key harmful elements P and S are significantly reduced, thereby meeting the requirements for the preparation of high-end high-temperature alloys. DETAILED DESCRIPTION

[0009] The ultrapure base material provided by the present invention comprises the following components in percentage by weight: C: 0.60-0.70%, Si≤0.02%, Mn≤0.01%, P≤0.0020%, S≤0.0006%, Al≤0.0050%, O≤0.0025%, N≤0.0040%, Cr≤0.04%, Mo≤0.04%, Cu≤0.04%, W≤0.03%, V≤0.01%, Ti≤0.0015%, and the balance is Fe and unavoidable impurities.

[0010] The production route of the ultra-pure base material with extremely low phosphorus, sulfur and aluminum content is: converter decarburization / phosphorus → slag removal → LF refining carbonization desulfurization → slag removal → RH vacuum degassing → continuous casting, and its main technologies are converter oxidation dephosphorization and LF refining desulfurization. The weight percentage of S at the end of combined blowing converter smelting is ≤0.0050%, and the weight percentage of P is ≤0.0015%; after LF refining, the weight percentage of S is ≤0.0005%, and the weight percentage of P is ≤0.0018%; after RH vacuum degassing, the weight percentage of S is ≤0.0006%, and the weight percentage of P is ≤0.0020%.

[0011] The double slag method is adopted for the removal of P in the combined blowing converter, in which the components of the primary slag system are: CaO: 40-50%; FeO: 15-20%; SiO2: 20-30%; MgO: <4%; the components of the secondary slag system are: CaO: 45-55%; FeO: 18-25%; SiO2: 10-20%; MgO: <4%. In the LF refining process, a deep desulfurization process is carried out under extremely low aluminum content conditions, and a deep desulfurization refining slag is invented, whose components are: CaO: 60-65%, SiO2: 12-18%, Al2O3: 10-15%, MgO: 4-6%, CaF2: 6-7%.

[0012] Specific implementation process: In order to obtain ultra-pure base materials with high carbon and extremely low content of harmful impurity elements such as phosphorus, sulfur, and aluminum for the preparation of high-end high-temperature alloys, it is necessary to overcome the interaction between dephosphorization, desulfurization, and low aluminum. According to the characteristics of high-carbon ultra-pure base materials, the present invention invents a process flow of converter decarburization / phosphorus → slag removal → LF refining carburization and desulfurization → slag removal → RH vacuum degassing → continuous casting to achieve the effect of deep dephosphorization and deep desulfurization under low aluminum conditions, and realize the stable production of ultra-pure base materials with extremely low sulfur, phosphorus, aluminum and other key contents under high carbon conditions.

[0013] Based on the ultrapure base material production method provided by the present invention, the key impurity elements S and P are controlled as follows: ① The weight percentage of S at the end of the combined blowing converter smelting is ≤0.0050%, and the weight percentage of P is ≤0.0015%; ② After LF refining, the weight percentage of S is ≤0.0005%, and the weight percentage of P is ≤0.0018%; ③ After RH vacuum degassing, the weight percentage of S is ≤0.0006%, and the weight percentage of P is ≤0.0020%. In this way, the prepared ultrapure base material product has sulfur ≤0.0006%, and phosphorus ≤0.0020%, which meets the requirements of high purity, high performance, and high-end high-temperature alloy preparation.

[0014] The converter smelting process of the present invention adopts a double slag method for smelting, and the double slag system of the converter smelting ultra-pure base material dephosphorization process is shown in the following table.

[0015]

[0016] In some preferred embodiments, in the primary slag making process, 35-45kg / t of lime, 20-25kg / t of lightly burned dolomite, 5-8kg / t of red mud balls, and 1.5-2.2kg / t of fluorite are added to the converter before adding iron. After blowing oxygen for 6-8 minutes, silicon and manganese oxidation is completed, and before carbon and oxygen are intensively oxidized, a slag pouring operation is performed. After the slag pouring is completed, the amount of slag in the furnace is ≤ 50% of the total amount of slag before slag pouring. After slag pouring, secondary slag making is performed, and 20-25kg / t of lime and 10-15kg / t of lightly burned dolomite are added to the secondary slag making. High-quality scrap steel is added during the converter blowing process for temperature control. Red mud balls, fluorite, and lime are added to the ladle in a ratio of 3:1:3 before the converter is tapped, and the amount added is controlled at 12-15kg / t according to the amount of molten steel. At the same time, argon is blown from the bottom of the ladle during the converter steel tapping process. After the steel tapping is completed, argon blowing and stirring are continued for 8-10 minutes, and the argon blowing intensity is controlled at 600-800Nl / min. After the argon blowing and stirring are completed, the slag in the ladle is removed by slagging, and the amount of residual slag after slagging is no more than 25% of the total slag.

[0017] The present invention also statistically analyzes the dephosphorization effects of the two processes of "converter single slag" and "converter double slag" for molten iron with an initial phosphorus content of 0.050%. The conventional converter single slag dephosphorization process can reduce the phosphorus content of the converter molten iron to 0.0060%, and the dephosphorization rate is 88.0%. The double slag dephosphorization of the present invention can control the final phosphorus content of the molten iron to ≤15ppm, and the dephosphorization rate is about 97%, which is 9% higher than the dephosphorization rate of the conventional single slag method.

[0018] Among them, the deep desulfurization process under the condition of extremely low aluminum content in the LF refining process invented the deep desulfurization refining slag, which includes, by mass percentage: CaO: 60-65%, SiO2: 12-18%, Al2O3: 10-15%, MgO: 4-6%, CaF2: 6-7%. If it is not involved in the claims here, please add it in the corresponding position of the claims.

[0019] After deep deoxidation and desulfurization operations are performed using the LF refined slag system of the present invention, the sulfur content in the steel is stably controlled at ≤0.0005%, while the sulfur content of similar steels smelted using other common refined slags is all greater than 0.0010%.

[0020] It should be noted that in the preparation method of the present invention, the parts not particularly described in each process are all carried out according to the prior art, and the present invention does not make any specific limitations on this.

[0021] On the other hand, the present invention also provides an ultrapure base material, which is prepared by the above-mentioned preparation method.

[0022] The ultrapure base material of the present invention comprises, by weight percentage: C: 0.60-0.70%, Si≤0.02%, Mn≤0.01%, P≤0.0020%, S≤0.0006%, Al≤0.0050%, O≤0.0025%, N≤0.0040%, Cr≤0.04%, Mo≤0.04%, Cu≤0.04%, W≤0.03%, V≤0.01%, Ti≤0.0015%, and the balance is Fe and unavoidable impurities.

[0023] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods without specific conditions in the following examples are based on conventional methods and conditions. Example 1

[0024] The trial production of "converter decarburization / phosphorus → slag removal → LF refining carbonization and desulfurization → slag removal → RH vacuum degassing → slab continuous casting" was adopted. The composition change process of ultra-pure base material for high-temperature alloy is shown in Table 4. The specific steps of each process are as follows: The converter adopts double slag method for smelting. In the first slag making process, 35kg / t of lime, 25kg / t of light-burned dolomite, 7.3kg / t of red mud balls, and 1.5kg / t of fluorite are added. After blowing oxygen for 6 minutes, the slag discharge amount is 60% of the total slag. Then the secondary slag making is carried out, adding 22kg / t of lime and 10kg / t of light-burned dolomite. Before the converter is tapped, 6kg / t of red mud balls, 2.0kg / t of fluorite, and 6kg / t of lime are added to the ladle in a ratio of 3:1:3 to make slag. The double slag composition of ultra-pure base material converter dephosphorization process is shown in Table 2.

[0025] Slag removal: In order to avoid excessive temperature drop of molten steel, the entire slag removal process is controlled within 20 minutes, and the amount of remaining slag after slag removal is 25% of the total slag.

[0026] LF refining: After entering the station, carbon powder is added for carbon blending, and then fluorite and lime are added in 6 batches, with a total amount of fluorite of 12kg / t steel, a total amount of lime added of 25kg / t, and a white slag time of 15min. The composition and basicity of the ultra-pure base material LF refining desulfurization slag system under low aluminum conditions are shown in Table 3.

[0027] Slag removal: In order not to affect the circulation of molten steel in the RH vacuum degassing process, slag removal is carried out according to the height of the refined slag after LF refining. The thickness of the slag in the ladle is controlled at 300mm after slag removal.

[0028] RH vacuum degassing: circulate at a vacuum degree of 10 mbar for 22 min.

[0029] Slab continuous casting: The slab continuous casting process adopts protective casting to prevent secondary oxidation, the superheat is controlled at 20-30℃, and the casting speed is determined according to the slab specifications. Example 2

[0030] The trial production of "converter decarburization / phosphorus → slag removal → LF refining carbonization and desulfurization → slag removal → RH vacuum degassing → slab continuous casting" was adopted. The composition change process of ultra-pure base material for high-temperature alloy is shown in Table 4. The specific steps of each process are as follows: The converter adopts double slag method for smelting. In the first slag making process, 40kg / t of lime, 22kg / t of light-burned dolomite, 5kg / t of red mud balls, and 1.8kg / t of fluorite are added. After blowing oxygen for 7 minutes, the slag discharge amount is 65% of the total slag. Then the secondary slag making is carried out, adding 20kg / t of lime and 12kg / t of light-burned dolomite. Before the converter tapping, 6.0kg / t of red mud balls, 2.0kg / t of fluorite, and 6.0kg / t of lime are added to the ladle in a ratio of 3:1:3 to make slag. The double slag composition of ultra-pure base material converter dephosphorization process is shown in Table 2.

[0031] Slag removal: The entire slag removal process is controlled within 22 minutes, and the amount of remaining slag after slag removal is 28% of the total slag.

[0032] LF refining: After entering the station, carbon powder is added for carbon blending, and then fluorite and lime are added in 7 batches, with a total amount of fluorite of 10kg / t and a total amount of lime of 22kg / t, and the white slag time is 17min. The composition and basicity of the ultra-pure base material LF refining desulfurization slag system under low aluminum conditions are shown in Table 3.

[0033] Slag removal: In order not to affect the circulation of molten steel in the RH vacuum degassing process, slag removal is carried out according to the height of the refined slag after LF refining. The thickness of the slag in the ladle is controlled at 450mm after slag removal.

[0034] RH vacuum degassing: circulate at a vacuum degree of 8 mbar for 20 min.

[0035] Slab continuous casting: The slab continuous casting process adopts protective casting to prevent secondary oxidation, the superheat is controlled at 20-30℃, and the casting speed is determined according to the slab specifications. Example 3

[0036] The trial production of "decarburization / phosphorus removal in converter → slag removal → LF refining and carbonization and desulfurization → slag removal → RH vacuum degassing → slab continuous casting" was adopted. The composition change process of ultra-pure base material for high-temperature alloy is shown in Table 4. The specific steps of each process are as follows: The converter adopts the double slag method for smelting. In the first slag making process, 45kg / t of lime, 20kg / t of light-burned dolomite, 8kg / t of red mud balls, and 2.2kg / t of fluorite are added. After blowing oxygen for 8 minutes, the slag pouring amount is 65% of the total slag. Then the secondary slag making is carried out, adding 25kg / t of lime and 15kg / t of light-burned dolomite. Before the converter is tapped, 6.0kg / t of red mud balls, 2.0kg / t of fluorite, and 6.0kg / t of lime are added to the ladle in a ratio of 3:1:3 to make slag. The double slag composition of the ultra-pure base material converter dephosphorization process is shown in Table 2.

[0037] Slag removal: In order to avoid excessive temperature drop of molten steel, the entire slag removal process is controlled within 25 minutes, and the amount of remaining slag after slag removal is 30% of the total slag.

[0038] LF refining: After entering the station, carbon powder is added for carbon blending, and then fluorite and lime are added in 8 batches, with a total amount of fluorite of 9kg / t and a total amount of lime of 20kg / t, and the white slag time of 20min. The composition and basicity of the ultra-pure base material LF refining desulfurization slag system under low aluminum conditions are shown in Table 3.

[0039] Slag removal: In order not to affect the circulation of molten steel in the RH vacuum degassing process, slag removal is carried out according to the height of the refined slag after LF refining. The thickness of the slag in the ladle is controlled at 400mm after slag removal.

[0040] RH vacuum degassing: circulate at a vacuum degree of 8 mbar for 20 min.

[0041] Slab continuous casting: The slab continuous casting process adopts protective casting to prevent secondary oxidation, the superheat is controlled at 20-30℃, and the casting speed is determined according to the slab specifications.

[0042]

[0043] The above description is only a specific embodiment of the present invention, but the structural features of the protection scope of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.

Claims

1. High carbon ultra-pure base material, characterized by: The mass percentages of its components are: C: 0.60-0.70%, Si≤0.02%, Mn≤0.01%, P≤0.0020%, S≤0.0006%, Al≤0.0050%, O≤0.0025%, N≤0.0040%, Cr≤0.04%, Mo≤0.04%, Cu≤0.04%, W≤0.03%, V≤0.01%, Ti≤0.0015%; the balance is Fe and unavoidable impurities.

2. A method for preparing a high carbon ultrapure base material, characterized in that: The following steps are involved: Step 1: Converter smelting: Double slag method is used for smelting: In the primary slag making process, 35-45kg / t of lime, 20-25kg / t of lightly burned dolomite, 5-8kg / t of red mud balls, and 1.5-2.2kg / t of fluorite are added to the converter before adding iron. After blowing pure oxygen for 6-8 minutes, silicon and manganese oxidation is completed and before carbon and oxygen are intensively oxidized, a slag pouring operation is performed. After the slag pouring is completed, the slag volume in the furnace is ≤ 50% of the total slag volume before slag pouring; after slag pouring, secondary slag making is performed. 20-25kg / t of lime and 10-15kg / t of lightly burned dolomite are added to the secondary slag making. The temperature of high-quality scrap steel, i.e. pure iron return material, is controlled to 1640-1670℃. Red mud balls, fluorite and lime are added to the ladle in a ratio of 3:1:3 before tapping the converter to make slag. The amount added is controlled at 12-15kg / t according to the amount of molten steel. At the same time, argon is blown from the bottom of the ladle during the converter tapping process. After the tapping is completed, argon blowing and stirring are continued for 8-10 minutes. The argon blowing intensity is controlled at 600-800Nl / min. After the argon blowing and stirring are completed, the slag in the ladle is removed by slagging. The amount of residual slag after slagging is not more than 25% of the total slag. The weight percentage of S at the end point of the combined blowing converter smelting is ≤0.0050%, and the weight percentage of P is ≤0.0015%; Step 2: LF refining: The LF treatment temperature is 1610-1630℃. During the LF refining process, 20-30kg / t of lime, 15-20kg / t of fluorite, Al particles and aluminum wire are added to make reducing slag for deoxidation and desulfurization to produce deep desulfurization refining slag. The deep desulfurization refining slag includes, by mass percentage, CaO: 60-65%, SiO2: 12-18%, Al2O3: 10-15%, MgO: 4-6%, CaF2: 6-7%. After LF refining, the weight percentage of S is ≤0.0005%, and the weight percentage of P is ≤0.0018%; Step 3: The slag removal process is controlled within 15-25 minutes, and the amount of slag left is 10-30mm; Step 4: RH vacuum degassing: the cycle time is 20-25min at a vacuum degree of 6-10mbar. After RH vacuum degassing, the weight percentage of S is ≤0.0006%, and the weight percentage of P is ≤0.0020%; Step 5: Continuous casting: Use 200mm×200mm-240mm×240mm billet for continuous casting. Protected casting is used in the process. The superheat is controlled at 20-30℃ and the pulling speed is controlled at 0.85-1.05m / min.

Citation Information

Patent Citations

  • Smelting technological process of low-silicon low-manganese ultrapure rotor steel

    CN102011059A

  • High-carbon industrial ultra-pure iron and preparation method thereof

    CN114058962A

  • High-cleanliness high-carbon steel and low-carbon-emission production method thereof

    CN116904863A

  • Ultra-pure base material, preparation method thereof and application of ultra-pure base material in preparation of high-end high-temperature alloy

    CN118127269A

  • Manufacture of high purity iron-carbon alloy

    JP1987174364A